Efecto de cuatro dosis de ácido- 3- Indol Butírico en el enraizamiento de ápices y segmentos nodales de Sacha Inchi ( Plukenetia Volubilis l. ) - Gárate Navarro, Mar Asunción (2009)
Aiming to contribute to the development of a protocol for in vitro clonal propagation of sacha inchi (Plukenetia volubilis L.), has been achieved through apices and nodal segments taken from in vitro conditions as ex vitro, establishing and determining the effect of four dose of acid - 3 - Indole butyric acid (IBA) (25, 50, 100 and 200 ppm) in the process of in vitro rooting of this species. Which were distributed in a completely randomized design with 2x4 factorial arrangement. All treatments showed a good number and root formation indicating that this species has great potential for development and good response to in vitro culture. Rooting for explants derived from in vitro conditions the highest number of roots per explant was observed at the T8 with an average of 8 roots, the longest root was at T7 with an average of 4.99 mm, while for the greatest number of roots per explant formed from callus was observed in T8 with an average of 7.25 roots, and the largest number of roots per explant produced directly from the woody tissue was observed at T3 (mean 4, 67 roots). Meanwhile, rooting for explants derived from ex vitro conditions, the highest number of roots per explant was observed at the T8 with an average of 5.25 roots, the longest roots were in the T2 with an average of 6 , 17 mm for the largest number of roots per explant formed from callus was observed in T8 with an average of 4.50 roots and the highest number of roots per explant produced directly from the woody tissue was observed with the T4 an average of 4.33 roots.